Lurking in the Shadows: Human Trafficking and Sex Work - Phillips, Jennifer M. (My University, 2021)
This thesis explores the issues surrounding human trafficking (HT) and exposes a great lack of knowledge about human trafficking by local, federal, and international law enforcement agencies. Human trafficking discourse generally spotlights sex trafficking (ST) because of its perceived cruel, frightening, and an inhumane treatment of people—rightfully so. Because of this focus, the issue of labor trafficking (LT) is often ignored. This is in part because a significant percentage of the world’s goods are unnoticeably produced through the use of labor trafficking, ranging from the fish you buy at the market to children’s sports equipment. Also examined within this thesis is how sex tourism affects cities where it is concentrated. While some countries have legalized sex work, underage prostitution is still illegal yet remains a common occupation.In the context of sex trafficking, this thesis will illuminate the extreme trauma victims face physically, mentally, emotionally, and spiritually. Using feminist theory, it will deconstruct the language and social constructs associated with trafficking to expose the troubling cause-and-effect relationship that marginalizes victims and protects the perpetrators. Due to the race, class, and gender bias prevalent in human trafficking discourse there remains an inadequate understanding of the topic. Lastly, as a result of improper training, healthcare providers and legal authorities unwittingly re-traumatize victims of human trafficking keep the guilty in power.
Keywords: Human trafficking; Prostitution; Sex tourism; Human trafficking; Labor trafficking; Sex tourism; Sex trafficking; Sex work; Trafficking; History